Analisis Statistical Quality Control dalam Proses Produksi Komponen Wheel Rim - Fitriana Fitriana; Fahriza Nurul Azizah; M Madyan Hamdi (Engineering Faculty at Universitas Singaperbangsa Karawang, 2023)
PT XYZ is a company engaged in the automotive component industry for Wheel Rims or rims for two-wheeled and four-wheeled vehicles for the domestic and export OEM markets. The Wheel Rim which was produced by PT XYZ in one month found 255 units of defective products. The types of damage are broken, slips, markings, and inappropriate sizes. So research is needed with a focus on quality control of the products produced. This study uses the Statistical Quality Control (SQC) method to analyze the level of wheel rim product defects and the factors that cause product damage so that the company can find solutions to overcome the damage that occurs and improve the quality of the products produced. The categories of defects with the highest number were broken defects (52%), followed by inappropriate sizes (31%), no markings (6%), inverted marks (5%), pinched (4%), and slips (2%). The results of the study show that the focus of the problem for the company is the number of broken defective products and inappropriate product sizes. The human factor is the main factor affecting the number of defective products, where the lack of accuracy and haste makes the production process not go well.